Additive Manufacturing of a Point‐of‐Care "Polypill:" Fabrication of Concept Capsules of Complex Geometry with Bespoke Release against Cardiovascular Disease. Issue 13 (8th June 2020) - Pereira, Beatriz C.; Isreb, Abdullah; Isreb, Mohammad; Forbes, Robert T.; Oga, Enoche F.; Alhnan, Mohamed A.
Abstract: Polypharmacy is often needed for the management of cardiovascular diseases and is associated with poor adherence to treatment. Hence, highly flexible and adaptable systems are in high demand to accommodate complex therapeutic regimens. A novel design approach is employed to fabricate highly modular 3D printed "polypill" capsules with bespoke release patterns for multiple drugs. Complex structures are devised using combined fused deposition modeling 3D printing aligned with hot‐filling syringes. Two unibody highly modular capsule skeletons with four separate compartments are devised: i) concentric format: two external compartments for early release while two inner compartments for delayed release, or ii) parallel format: where nondissolving capsule shells with free‐pass corridors and dissolution rate‐limiting pores are used to achieve immediate and extended drug releases, respectively. Controlling drug release is achieved through digital manipulation of shell thickness in the concentric format or the size of the rate limiting pores in the parallel format. Target drug release profiles are achieved with variable orders and configurations, hence confirming the modular nature with capacity to accommodate therapeutics of different properties. Projection of the pharmacokinetic profile of this digital system capsules reveal how the developed approach can be applied in dose individualization and achieving multiple desired pharmacokinetic profiles. Abstract : A novel design approach is employed to fabricate highly modular 3D printed "polypill" capsules with bespoke release patterns for multiple drugs. Complex structures are devised to achieve dose individualization. In silico pharmacokinetic projections of the developed capsules highlight how healthcare staff can adapt complex therapeutic regimens to each patient.